A comparison of decontamination effects of commercially available detergents in rats pre-exposed to topical sulphur mustard. (June 2013) - Misik, Jan; Jost, Petr; Pavlikova, Ruzena; Vodakova, Eva; Cabal, Jiri; Kuca, Kamil
<x xml:space="preserve">Abstract</x> Objective: The genotoxic vesicant sulphur mustard [bis-2-(chloroethyl)sulphide] is a chemical warfare agent which is easily available due to its relatively simple synthesis. Thus, sulphur mustard is a potential agent for mass contamination. In this study, we focused on sulphur mustard toxicity and decontamination in a rat model using commercially available detergent mixtures for dermal decontamination. Methods: Male Wistar rats were percutaneously treated with sulphur mustard and subjected to wet decontamination 2 min postexposure. Commercially produced detergents Neodekont™, Argos™, Dermogel™ and FloraFree™ were tested for their decontamination efficacy against an exposed group and their protective ratios determined. Results and conclusion: The results showed that all tested detergent solutions produced an increase in the median lethal dose [LD50 = 9.83 (5.87–13.63) mg·kg−1] in comparison to controls, which led to increased survival of experimental animals. In general, all tested detergents provided modest decontamination efficacy (PR = 2.0–5.7). The highest protective ratio (5.7) was consistently achieved with Argos™. Accordingly, Argos™ should be considered in further investigation of mass casualty decontamination.